2014
DOI: 10.1096/fj.14-260182
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of ADORA2B from myeloid cells dampens lung fibrosis and pulmonary hypertension

Abstract: Idiopathic pulmonary fibrosis (IPF) is a lethal, fibroproliferative disease. Pulmonary hypertension (PH) can develop secondary to IPF and increase mortality. Alternatively, activated macrophages (AAMs) contribute to the pathogenesis of both IPF and PH. Here we hypothesized that adenosine signaling through the ADORA2B on AAMs impacts the progression of these disorders and that conditional deletion of ADORA2B on myeloid cells would have a beneficial effect in a model of these diseases. Conditional knockout mice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
97
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(107 citation statements)
references
References 43 publications
10
97
0
Order By: Relevance
“…suggests that A 2B R may exist as a multiprotein complex in intestinal epithelia [39], which may result in varying downstream effects depending on interactions with various stimuli. Inflammation typically entails activation of immune cells and induction of cytokines, which has been reflected in the role of A 2B R in myeloid cells [22, 40]. Pulmonary A 2B Rs appear to modulate a localized inflammatory response involving enhanced secretion of chemokines and cytokines, which is consistent with our results in the lung IRI model in which A 2B R antagonism attenuated the induction of pro-inflammatory cytokines after IR.…”
Section: Commentsupporting
confidence: 87%
“…suggests that A 2B R may exist as a multiprotein complex in intestinal epithelia [39], which may result in varying downstream effects depending on interactions with various stimuli. Inflammation typically entails activation of immune cells and induction of cytokines, which has been reflected in the role of A 2B R in myeloid cells [22, 40]. Pulmonary A 2B Rs appear to modulate a localized inflammatory response involving enhanced secretion of chemokines and cytokines, which is consistent with our results in the lung IRI model in which A 2B R antagonism attenuated the induction of pro-inflammatory cytokines after IR.…”
Section: Commentsupporting
confidence: 87%
“…46,47 In addition, accumulating evidence shows that macrophages, T cells, and progenitor cells are recruited in the lesions contributing to vascular remodeling. 4749 It has also been shown that HIF- stimulated extracellular adenosine production and signaling affect the pathogenesis of PH through modulation of macrophage functional polarization 50 . Given the observation of induced CXCL12 expression in PHD2-deficient ECs, PHD2 deficiency in ECs may also promote bone marrow cell recruitment to the lung and thereby induces complex vascular remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…If true, this would be an extremely important concept because this novel idea would suggest that administration of A 1 receptor antagonists would be protective in patients with a high A 1 to A 2B ratio, whereas an A 2B receptor agonist would be preferred in patients with a high A 2B to A 1 ratio (i.e., personalized medicine). However, a caveat is that A 2B receptors when activated chronically can induce pro-fibrotic and pro-inflammatory effects 62, 63 . Therefore, it may be important to limit the duration of treatment with A 2B receptor agonists to just the critical time period in which HCASMC proliferation occurs in response to injury.…”
Section: Discussionmentioning
confidence: 99%
“…Given that A 1 receptors have much higher affinity for adenosine, why would their effect not predominate? There are reports that A 1 receptors form heterodimers with A 2A receptors and β-adrenoceptors, and that heterodimer formation blocks A 1 receptor signaling 62, 63 . Therefore, one possibility is that in HCASMCs A 2B receptors directly block A 1 receptor signaling via heterodimerization.…”
Section: Discussionmentioning
confidence: 99%